The Role of Human Resource Management in Conducting CSR at an IT Company in Indonesia - Hakim, Arif Rahman; Pasaribu, Arta Monica; Rahmat, Muhamad Nur (AIBPM Publisher, 2024)
This study delves into the role of Human Resource Department in corporate social responsibility (CSR) initiatives at PT. Sigma Cipta Caraka (hereinafter: Telkomsigma). Through a qualitative analysis, the current practices of human resources concerning the corporate social responsibility programs at the company were scrutinized. The results indicate that the management of these programs predominantly falls under the purview of the Corporate Communications department, with minimal engagement from human resources department. To enhance the efficacy of the program initiatives and cultivate a more cohesive approach to social responsibility within the organization, fostering collaboration between Human Resources and Corporate Communications is imperative. By bridging these departments and aligning their efforts, Telkomsigma can optimize the impact of its CSR endeavors and reinforce its commitment to sustainable and socially responsible practices. This study underscores the significance of inter-departmental cooperation in driving meaningful the CSR outcomes and advancing the company's overarching goals of community engagement and environmental stewardship. The findings reveal that the programs are primarily managed by the Corporate Communications division, with limited involvement from human resources. Enhancing collaboration between the Human Resources and Corporate Communications can improve the effectiveness of this program initiatives and foster a more integrated approach to social responsibility within the organization.